THE PATIENTS' CHARACTERISTICS AND NON-SURGICAL TREATMENT RESULTS FOR HYPOPHARYNGEAL CANCER IN SOUTHEAST OF IRAN: A 13-YEAR STUDY - Larizadeh, Mohammad Hasan; Aliasghar Arabi-Mianroodi,; Hadi Eslami, (Journal of Ayub Medical College Abbottabad, 2023)
Background: Various modalities have been used to treat hypopharyngeal cancer. Non- surgical modalities include radiotherapy alone, sequential chemoradiation and concomitant chemoradiation or bio radiation. This study was conducted to evaluate the primary non-surgical treatment. Methods: A total number of 67 patients treated from March 2009 to January 2022 were enrolled in this study. The 2-year and 5-year survival rates were estimated using the Kaplan-Meier method. Log-rank test was used to compare the survival outcomes according to various factors. To define independent prognostic factors, we used Cox regression analysis. Results: The mean age of the patients was 56.2 years, and 55.2% of them were male. These patients were treated by radiation alone (9 patients) or induction chemotherapy followed by either radiation (4 patients), chemoradiation (33 patients), or bio-radiation (21 patients). The mean follow-up time was 18.12 months. The 2-year and 5-year overall survival rates were estimated to be 43% and 18%, respectively. Multivariate analysis showed that T stage, N stage, and treatment modality had a statically significant relationship with overall survival. Conclusion: The results of non-surgical treatment for hypopharyngeal cancer are not satisfactory. More studies are needed to investigate the role of salvage surgery.